2017
DOI: 10.1158/1538-7445.am2017-4208
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4208: Inhibition of proliferation and induction of apoptosis by a novel phytobiological mixture against breast cancer cell lines

Abstract: Breast cancer remains a leading cause of women’s death worldwide with progressive emergence of resistance towards approved chemotherapies. For this reason, new complementarytreatments have been sought. One of those includethe use of a phytobiological mixture against different types of malignancies, including but not limited to breast cancer. Herein, we investigated the anti-proliferative effects of a novel phytobiological mixture (PB)against two breast cancer cell lines :MDA-MB-231 and MCF-7.The PB mixture is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The annexin V/PI assay with flow cytometry showed that PB induced the pro-apoptotic effect in HCT116 cells in a concentration dependent manner at 24 h. At the highest concentration of 150 ug/mL, the percentage of annexin V positive cells stood at 28.55%. Our findings are in accordance with the previous studies that reported that the exposure of MDA-MB-231 breast cancer cells to PB resulted in the induction of apoptosis in a concentration-dependent manner (Alqarni et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The annexin V/PI assay with flow cytometry showed that PB induced the pro-apoptotic effect in HCT116 cells in a concentration dependent manner at 24 h. At the highest concentration of 150 ug/mL, the percentage of annexin V positive cells stood at 28.55%. Our findings are in accordance with the previous studies that reported that the exposure of MDA-MB-231 breast cancer cells to PB resulted in the induction of apoptosis in a concentration-dependent manner (Alqarni et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
“…It can be inferred that at higher concentrations, PB may have arrested the replication of DNA and hence prevented the cells to enter into the G2 phase leading to the decreased cell division and overall inhibitory effect on the cancer cell growth. Previous studies have also reported that exposure of MDA-MB-231 to concentrations of PB of 10 ug/mL and 30 ug/mL resulted in a significant cell cycle arrest at the G1/S phase with a population of 25.3 ± 1.6% and 20.5 ± 0.4%, respectively, as compared to the control untreated cells 12.4±1.5% (p<0.001) (Alqarni et al, 2017). However, further molecular studies at the protein and gene level are necessary which can enable us to arrive at a concrete decision.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation